Improving the Atmosphere of Sunday Worship Through Music Services at GKI Hermon Hollo Him - Nanuru, Cerry Fressly; Sulistyowati, Ambar; Sahureka, Cosye M.; S. Marlissa, , Magdalena; Mulder, Deysi O.; Bidang, Aris; Polhaupessy, Yustinus; Parinussa, Nelinio; Kadir, Yori R.; Parabang, Alfaris P. (Abdi Masyarakat, 2024)
Community Service Activities (PkM) by the Church Music Department at GKI Hermon Hollo Him aims to improve the atmosphere of Sunday worship through the integration of various musical elements. The main problem faced is the lack of music that can touch the hearts of the congregation and deepen their spiritual experience. This activity is also a vehicle to enrich the worship experience by using musical ensembles, soloists, song leaders and keyboard players. The method used is demonstration, where lecturers and students apply their musical knowledge in Sunday services at the church. The results of the activity showed a significant increase in the quality of worship music. The ensemble's musical performance combines instruments such as keyboard, violin, flute, and saxophone, along with a medley of Kidung Jemaat 387 and Papuan folk songs, creating a deep harmony that enriches the worship experience and celebrates cultural richness. The soloist's appearance and support from the keyboard player add an emotional and spiritual dimension. Song leaders also play an important role in leading the congregation, creating togetherness and quality song delivery. In conclusion, this PkM succeeded in deepening the spiritual experience and improving the atmosphere of worship at GKI Hermon Hollo Him as a whole.